Implementasi Inkubator Penetas Telur Ayam Berbasis IoT Menggunakan Aplikasi Blynk - Triyanto, Aripin; Kusnadi, Heri (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Entrepreneurship in free-range chicken meat is promising for business an entrepreneur. With a high level of interest in meat, you can make a profit. The problem experienced by chicken farmers is that the condition of the chicken eggs that hatch deeply is not seen continuously due to the large number of them, and the lack of attention to temperature when the eggs are hatched. The solution used is to make egg incubator equipment and record the results of hatching eggs, thereby reducing the failure hatching failure rate and the chickens' safety hatch. The use of the method is to analyze the comparison of natural hatching of eggs from hens by comparing the hatching of eggs using incubator equipment. The use of equipment in the incubator includes NodeMCU ESP 8266 as a processor, Current Sensors, Ultrasonic sensors, and lamps as incubator heaters. The aim of the research is to maintain the stability and hatching time of the eggs. Besides that, it can help human performance by recording the time of hatching eggs so there is no loss. This research produced incubator equipment equipped with an IoT system with adjustable temperatures ranging from 380C to 400C using two lamps as heaters and fans as coolers. The average time needed by the heater to raise the temperature from 380C to 40oC is 55 seconds. Tool equipment, namely there is a notification using an ultrasonic sensor that functions as a Buzzer switch when there are chicks in it.